The Burden of Cryptosporidium Diarrheal Disease among Children < 24 Months of Age in Moderate/High Mortality Regions of Sub-Saharan Africa and South Asia, Utilizing Data from the Global Enteric Multicenter Study (GEMS). - Samba O Sow; Khitam Muhsen; Dilruba Nasrin; William C Blackwelder; Yukun Wu; Tamer H Farag; Sandra Panchalingam; Dipika Sur; Anita K M Zaidi; Abu S G Faruque; Debasish Saha; Richard Adegbola; et al. (PLoS Neglected Tropical Diseases)
Background The importance of Cryptosporidium as a pediatric enteropathogen in developing countries is recognized. Methods Data from the Global Enteric Multicenter Study (GEMS), a 3-year, 7-site, case-control study of moderate-to-severe diarrhea (MSD) and GEMS-1A (1-year study of MSD and less-severe diarrhea [LSD]) were analyzed. Stools from 12,110 MSD and 3,174 LSD cases among children aged <60 months and from 21,527 randomly-selected controls matched by age, sex and community were immunoassay-tested for Cryptosporidium. Species of a subset of Cryptosporidium-positive specimens were identified by PCR; GP60 sequencing identified anthroponotic C. parvum. Combined annual Cryptosporidium-attributable diarrhea incidences among children aged <24 months for African and Asian GEMS sites were extrapolated to sub-Saharan Africa and South Asian regions to estimate region-wide MSD and LSD burdens. Attributable and excess mortality due to Cryptosporidium diarrhea were estimated. Findings Cryptosporidium was significantly associated with MSD and LSD below age 24 months. Among Cryptosporidium-positive MSD cases, C. hominis was detected in 77.8% (95% CI, 73.0%-81.9%) and C. parvum in 9.9% (95% CI, 7.1%-13.6%); 92% of C. parvum tested were anthroponotic genotypes. Annual Cryptosporidium-attributable MSD incidence was 3.48 (95% CI, 2.27-4.67) and 3.18 (95% CI, 1.85-4.52) per 100 child-years in African and Asian infants, respectively, and 1.41 (95% CI, 0.73-2.08) and 1.36 (95% CI, 0.66-2.05) per 100 child-years in toddlers. Corresponding Cryptosporidium-attributable LSD incidences per 100 child-years were 2.52 (95% CI, 0.33-5.01) and 4.88 (95% CI, 0.82-8.92) in infants and 4.04 (95% CI, 0.56-7.51) and 4.71 (95% CI, 0.24-9.18) in toddlers. We estimate 2.9 and 4.7 million Cryptosporidium-attributable cases annually in children aged <24 months in the sub-Saharan Africa and India/Pakistan/Bangladesh/Nepal/Afghanistan regions, respectively, and ~202,000 Cryptosporidium-attributable deaths (regions combined). ~59,000 excess deaths occurred among Cryptosporidium-attributable diarrhea cases over expected if cases had been Cryptosporidium-negative. Conclusions The enormous African/Asian Cryptosporidium disease burden warrants investments to develop vaccines, diagnostics and therapies.